Persian-Turkish Bilingual Children’s Responses to Forced-Choice Questions - Behzadnia, Ali; Mehrani, Mehdi B. (Current psychology (New Brunswick, N.J.), 2020)
The present study aimed to investigate how Persian-Turkish bilingual children tend to respond to forced-choice questions pertaining to objects. A total of 42 bilingual 5- and 6-year-old children were asked two-option forced-choice questions about a set of four familiar and four unfamiliar objects. The analysis of participants’ responses showed that older preschoolers are less susceptible to two-option forced-choice questions. That is, 5- and 6-year-old bilingual preschoolers are less likely to show a recency tendency unless they are asked about unfamiliar objects. Overall, the results evidenced that children’s familiarity with objects influenced their responses, whereas children’s language did not have any impact on their responses. The implications of the findings are discussed.